Traditional healers as caregivers to HIV/AIDS clients and other terminally challenged persons in Kanye community home-based care programme (CHBC), Botswana - S. M. Kang'ethe (Taylor & Francis Group, 2009)
The research study done at the Kanye village of Botswana was qualitative in design and exploratory in nature. While the broad goal aimed at assessing the contributions of caregivers in the Kanye CHBC programme, this article aims at evaluating the traditional healers' contribution as providers of care to HIV/AIDS patients and other chronically ill persons. The study conveniently involved all the 140 registered caregivers in the Kanye programme, but with only 82 caregivers turning up for focus group discussions. The caregivers were grouped in 10 focus group discussions, and all of the 5 CHBC nurses were subjected to one-on-one interviews. Both the focus group discussions and one-on-one interviews with the nurses used two slightly different interview schedules as data collection instruments. The study findings revealed that traditional healers are important players in caregiving of persons with various ailments but their role, position and contribution in the battle against HIV/AIDS is fast waning with time. The government has been challenged to map out strategies of collaboration between the two systems as traditional healers can complement the services of biomedical practitioners in this era of HIV/AIDS.